2008
DOI: 10.1016/j.expneurol.2008.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Midline brain injury in the immature rat induces sustained cognitive deficits, bihemispheric axonal injury and neurodegeneration

Abstract: Infants and children less than 4 years old suffer chronic cognitive deficits following mild, moderate or severe diffuse traumatic brain injury (TBI). It has been suggested that the underlying neuropathologic basis for behavioral deficits following severe TBI is acute brain swelling, subarachnoid hemorrhage and axonal injury. To better understand mechanisms of cognitive dysfunction in mild-moderate TBI, a closed head injury model of midline TBI in the immature rat was developed. Following an impact over the mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
79
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 36 publications
6
79
2
Order By: Relevance
“…It is critical to specifically examine pediatric patients, as the semi-acute injury response and recovery trajectories following mTBI are likely to be different for the immature and mature brain (Suskauer and Huisman, 2009). For example, both animal (Bayly et al, 2006;Huh et al, 2008) and human (Hessen et al, 2007) studies have shown that the developing brain may be more susceptible than the developed brain to mild diffuse brain injury (Adelson and Kochanek, 1998;Levin, 2003). Finally, our current results also demonstrate that fMRI is more sensitive to the effects of mTBI than behavioral, neuropsychological, and traditional MRI measures, and they underscore the promise of fMRI for elucidating the potential neural substrates of subtle cognitive deficits associated with this condition.…”
supporting
confidence: 60%
“…It is critical to specifically examine pediatric patients, as the semi-acute injury response and recovery trajectories following mTBI are likely to be different for the immature and mature brain (Suskauer and Huisman, 2009). For example, both animal (Bayly et al, 2006;Huh et al, 2008) and human (Hessen et al, 2007) studies have shown that the developing brain may be more susceptible than the developed brain to mild diffuse brain injury (Adelson and Kochanek, 1998;Levin, 2003). Finally, our current results also demonstrate that fMRI is more sensitive to the effects of mTBI than behavioral, neuropsychological, and traditional MRI measures, and they underscore the promise of fMRI for elucidating the potential neural substrates of subtle cognitive deficits associated with this condition.…”
supporting
confidence: 60%
“…When tested for cognitive performance in the BM, both injury groups showed cognitive impairment consistent with findings in previous brain injury studies. 25,30,31,42,44,45 There was a worsening trend for r-mTBI compared with s-mTBI during the acquisition trials as well as on time to zone in the probe trial, and on the final day of acquisition training the r-mTBI group performed significantly worse than the other three groups.…”
Section: Discussionmentioning
confidence: 90%
“…By 10 days postinjury (s-mTBI-10D) there was no evidence for APP immunoreactivity, consistent with the current literature for animal models in that strong APP staining is present at 24 h post-injury, 22,30,47 which diminishes by 14 days post-injury. 42,46 In the r-mTBI group, more widespread damage was observed, with immunoreactive axons also evident in the spinal trigeminal tracts of the BS and beneath the impact site in the form of APP immunoreactive neuronal perikaryas. However, in the r-mTBI group, the APP immunoreactive axonal swellings were less frequent and less robustly stained in the CC than those observed at 24 h after s-mTBI.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…65 Midline brain injury in immature rats led to diffuse neurodegeneration in both hemispheres that was felt to be responsible for the sustained cognitive deficits observed in these animals. 66 In our model, we used unilateral injury to the parietal cortex, which led to significant cognitive deficits and delay in developmental maturation. These findings are consistent with other rodent models with parietal cortex injury.…”
Section: Comparison With Other Models and Translational Relevancementioning
confidence: 99%